2021
DOI: 10.1186/s12889-020-10052-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between stroke occurrence and changes in atmospheric circulation

Abstract: Background The impact of weather on morbidity from stroke has been analysed in previous studies. As the risk of stroke was mostly associated with changing weather, the changes in the daily stroke occurrence may be associated with changes in atmospheric circulation. The aim of our study was to detect and evaluate the association between daily numbers of ischaemic strokes (ISs) and haemorrhagic strokes (HSs) and the teleconnection pattern. Methods Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…We found a different and significant effect of strong and moderate ENSO on stroke. Our findings provide additional insight into a similar association in Lithuania where some evidence was found on a link between atmospheric circulation and health (Venclovienė et al 2021 ). The weather conditions during the period of a strong El Niño were different as compared to the period of a moderate El Niño.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We found a different and significant effect of strong and moderate ENSO on stroke. Our findings provide additional insight into a similar association in Lithuania where some evidence was found on a link between atmospheric circulation and health (Venclovienė et al 2021 ). The weather conditions during the period of a strong El Niño were different as compared to the period of a moderate El Niño.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, it is thought that changes in atmospheric pressure may lead to a plaque rupture in the carotid arteries (Houck et al 2005). Studies on thrombosis in air travel suggest that prothrombin fragments and the thrombin-antithrombin complex are activated in hypobaric conditions (Gungor and Onar 2007;Schreijer et al 2006), which could be another clue to the underlying mechanism (Vencloviene et al 2021). The results obtained in previous studies showed different and controversial effects of atmospheric pressure on HS and IS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations